2006
DOI: 10.1017/bjn20061952
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary counselling on nutrient intake during pregnancy: a prospective cohort study

Abstract: The aim of this study was to assess the impact of dietary counselling combined with the provision of food products on food and nutrient intake in pregnant women. We carried out a prospective cohort study of healthy and atopic pregnant women (n 209), who were randomized into dietary intervention and control groups. The intervention group received dietary counselling and food products to modify the fat composition of their diet to meet current recommendations. Three-day food records were collected during each tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
92
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(103 citation statements)
references
References 38 publications
(51 reference statements)
5
92
0
5
Order By: Relevance
“…This finding draws attention to the need for improved nutrition education and behavioral modification techniques to support a healthy lifestyle and prevent excess weight gain during pregnancy. Individualized dietary and exercise screening and counseling can change maternal dietary and physical activity behavior and yield improved results for maternal and child health [6,8,10]. Currently, prenatal nutrition counseling and dietary assessment services are not uniformly available and may not be covered by all medical insurance plans [1].The cost for implementing these programs widely is a challenge that has yet to be solved, though the need is evident.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This finding draws attention to the need for improved nutrition education and behavioral modification techniques to support a healthy lifestyle and prevent excess weight gain during pregnancy. Individualized dietary and exercise screening and counseling can change maternal dietary and physical activity behavior and yield improved results for maternal and child health [6,8,10]. Currently, prenatal nutrition counseling and dietary assessment services are not uniformly available and may not be covered by all medical insurance plans [1].The cost for implementing these programs widely is a challenge that has yet to be solved, though the need is evident.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of dietary education during pregnancy is reflected by a study that found that 72% of pregnant women who had an 'unhealthy' dietary pattern early in pregnancy continued to eat the same way in their second trimester and 57% in the third trimester [6,7]. Food choices were shown to effectively change in pregnant women when they were provided with a combination of dietary counseling and healthy food products, as evidenced by increases in the number of servings of vegetables, fruits, soft margarines and vegetable oils and decreases in butter consumption [8]. As a result, dietary intake significantly improved by increasing nutrients such as polyunsaturated fatty acids, dietary fiber, vitamin E, folate and ascorbic acid intake and decreasing saturated fatty acid intake [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From our prospective study, we have thus far learned that by modifying the dietary intake of fat and fibre by detailed dietary counselling and by the provision of appropriate food products combined with probiotics, we are not only improving the quality of the maternal diet (Piirainen et al, 2006) but also the maternal glucose metabolism up to 1 year after pregnancy (Laitinen et al, 2009). In the present study, the risk reduction in infants' high 32-33 split proinsulin concentration was already detected at the age of 6 months, although, the intervention did not influence the infants' adiposity measurements or leptin/adiponectin ratio.…”
Section: Discussionmentioning
confidence: 99%
“…Todo estos factores pueden aumentar el riesgo de complicaciones perinatales debido a un estado de malnutrición (1,6,7). Existen estudios que demuestran que las recomendaciones dietéticas que se entregan en la consulta de la matrona, junto con las modificaciones en el estilo de vida que la embarazada llegue a implementar en el periodo gestacional, son intervenciones efectivas para mejorar el metabolismo materno y prevenir las complicaciones del embarazo, especialmente en mujeres embarazadas con déficit nutricional o con aumento de peso (8,9). Además, a toda gestante se debe le recomendar la práctica diaria de actividad física, siempre que no exista una contraindicación clara para ello.…”
Section: Introductionunclassified